Characterization of Thermotolerant Acetic Acid Bacteria Isolated from Various Plant Beverages in Thailand - Charee, Panadda; Tanamool, Varavut; Toyama, Hirohide; Soemphol, Wichai (Applied Food Biotechnology, 2020)
Background and objective: Thermotolerant acetic acid bacteria are more resistant to high temperatures than that other bacteria are. This difference includes 5-10ºC, which decreases high costs of cooling systems needed for the growth of these bacteria while preserving their high productivity. In this study, effective thermotolerant acetic acid bacteria isolated from various fermented plant beverages were characterized for their ability to produce acetic acid and their characteristics were investigated. Materials and methods: Various thermotolerant acetic acid bacteria isolated from fermented plant beverages samples were investigated for their ability to produce acetic acid at high temperature. Two isolates of Acetobacter pasteurianus were selected and their growth and acetic acid production ability were assessed under various conditions. Furthermore, capsular polysaccharides of these strains were extracted and characterized using gas-liquid chromatography and Fourier-transform infrared spectroscopy. Results and conclusion: In this study, Acetobacter pasteurianus and Acetobacter tropicalis were dominant thermotolerant acetic acid bacteria in the fermented plant beverage. Two isolates of Acetobacter pasteurianus, Fermented Plant Beverages 2-3 and 2-16, produced acetic acid effectively at 39°C, compared to that Acetobacter pasteurianus SKU1108 did as a superior control for thermotolerant acetic acid bacteria. Fermented Plant Beverage 2-3 was able to completely oxidize 5% v v-1 ethanol to acetic acid at 39°C, while a long lag time was observed at 6% ethanol. However, production of acetic acid was still up to 4% w v-1. Moreover, this isolate exhibited excellent resistance to acetic acid at high temperatures, compared to 2 other strains in liquid and solid media. However capsular polysaccharides isolated from the 3 strains included glucose, rhamnose and galactose. Fourier-transform infrared spectroscopy spectra of capsular polysaccharides from Fermented Plant Beverage 2-3 at 1740 cm-1 identified a clearly different O-acetyl ester. This might be attributed to different O-acetyl ester contents of the capsular polysaccharides and also to resistance to acetic acid and high temperature. Conflict of interest: The authors declare no conflict of interest.